Changes in photosynthetic pigments and chlorophyll fluorescence parameters in the super-high-yielding rice hybrid Peiai64S/E32 during senescence - L.D. ZENG (Photosynthetica, 2020)
The hybrid rice (Oryza sativa L.) cultivar Peiai64S/E32, which is a hybrid of E32 and Peiai64S, has a super high yield compared with that of its parents. Changes in photosynthetic pigments and chlorophyll (Chl) fluorescence parameters were investigated in the flag leaves during senescence. The content of Chl and carotenoids in the flag leaves of Peiai64S/E32 was more stable than those of their parents during senescence. Furthermore, Peiai64S/E32 had a more stable PSII activity and a lower nonphotochemical quenching and deepoxidation state than that of its parents in the later stage of senescence. These results demonstrated that Peiai64S/E32 functioned longer than its parents did during the leaf senescence and grain-filling period. This occurred because there was more excitation energy to drive photosynthetic CO2 fixation in Peiai64S/E32, as the pigments supplying the energy survived longer in the high-yielding rice compared to the parents.